2021
DOI: 10.3390/jcs5090246
|View full text |Cite
|
Sign up to set email alerts
|

Laser Butt Welding of Thin Ti6Al4V Sheets: Effects of Welding Parameters

Abstract: Titanium and its alloys, particularly Ti6Al4V, which is widely utilized in the marine and aerospace industries, have played a vital role in different manufacturing industries. An efficient and cost-effective way of joining this metal is by laser welding. The effect of laser power and welding speed on the tensile, microhardness, and microstructure of Ti6Al4V alloy is investigated in this paper. Results show that the microhardness is highest at the fusion zone and reduces towards the base metal. The microstructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…3. It was observed that the tensile strength of the R sample (957 MPa) matched the values given in the literature [61,62].…”
Section: Tensile Tests and Vickers Hardnesssupporting
confidence: 80%
See 1 more Smart Citation
“…3. It was observed that the tensile strength of the R sample (957 MPa) matched the values given in the literature [61,62].…”
Section: Tensile Tests and Vickers Hardnesssupporting
confidence: 80%
“…These values can be considered as standard for Ti-6Al-4V alloy. Omoniyi et al [62] joined Ti-6Al-4V sheets with 2.6-2.8 kW power values using laser welding. Vickers hardness measurements showed that the BM was 343 ± 12 HV0.5 and the weld zones were 426 ± 17 HV0.5.…”
Section: Tensile Tests and Vickers Hardnessmentioning
confidence: 99%
“…Similar to the FZ of AM welds, coarse columnar grains exist within the FZ of the wrought welds with an average length of 43.3 µm, as shown in Fig. 8 c. The grains appear like the needle-like α lamellar and acicular α’, resulting from the zone reaching the liquidus temperature and cooling at a rate above the critical cooing rate of 410 °C/s as explained and also observed in 36 38 . The length of the columnar grains is close to that of the AM welds.…”
Section: Resultssupporting
confidence: 61%
“…Welding is a material-joining process that produces the fusion of materials by heating the material to melting temperatures [1,2]. Permanent joints are achieved by welding processes [3].…”
Section: Introductionmentioning
confidence: 99%